Analysis of Chicken Meat Supply Chain in Dua Putra Perkasa Pratama Company (Inc.) - Annisa Maulina Wardhani; Titik Ekowati; Wiludjeng Roessali (SOCA: Jurnal Sosial Ekonomi Pertanian, 2020)
Supply chain analysis required in the entire business process because it produced a more sufficient product on the producer to the consumer level with the precise condition, time, and amount of product. This study purpose was to analyze the main product flow, mechanism, and supply chain performance of the chicken meat produced by the Dua Putra Perkasa Pratama Company (Inc.) The study location was chosen by a purposive sampling technique, while the participant selection done by judgment sampling technique. The participants were the supplier, key informant from the company, and customer. The supply chain, mechanism, and performance data analyzed by descriptive analysis method with the Supply Chain Operations Reference (SCOR) model. Results showed that the flow of the supply chain, financial supply chain, and informational was moving from the upstream to downstream, downstream to upstream, and upstream to downstream or downstream to upstream, respectively. The company supply chain performance classified in a very good range performance with a total score of 96.73.